Offshore platform rigid riser span analysis and experimental studies - Ong, Yean Chau (2010)
A rigid riser mechanically clamped to an offshore wellhead platform experiences vortex induced vibration due to action of seawater waves and currents. If occuring at the natural frequency of free span, it will induce a large amplitude vibration that may lead to fatigue failure at the girth welds of pipe joints. To assess if the maximum riser span between the clamps is acceptable, the current practice is to determine based on the same methodology for analyzing the free span of submarine pipelines on the seabed. These methods for assessment have been well described in detail in the MULTISPAN project carried out by Norsk Agip and Statoil (Mark, Vitali and Verley, 1997) and subsequently in Det Norske Veritas (DNV)standards, Guidelines No. 14 and DNV-RP-F105.